A PILOT STUDY OF THE ACCEPTANCE AND TOLERABILITY OF TUMOUR TREATING FIELDS IN ADULT GLIOBLASTOMA PATIENTS. (3rd October 2018) - Brodbelt, Andrew; Williams, Matthew; Thorpe, Antonia; Mills, Samantha; Price, Stephen; Lekka, Elvira; Watts, Colin; Davis, Charles; Jenkinson, Michael
Abstract: BACKGROUND: Tumour treating fields are a novel anticancer treatment that uses alternate electrical fields to disrupt cell division. It has been shown in a randomized controlled trial to significantly improve survival in patients with Glioblastoma. Use of the device is intensive for patients, with almost constant electrode application and battery use. The acceptability and tolerability for this new treatment is not known in a UK setting. The treatment currently costs €21, 000 per month. METHODS: Three UK centres were offered support for trialling the treatment. Patients with proven MGMT unmethylated glioblastoma, had completed Stupp, had a performance score >70, and had social support (for placing the electrodes), where approached. Monthly assessments of compliance and quality of life (QOL) (ECOG BT 30), and quarterly MRIs and tolerability questionnaires were completed. RESULTS: Oncologists in one centre refused to support any use of the device, so no patients were approached in that centre. 8 patients were approached in the other two centres, 5 accepted, and 1 further patient had treatment started elsewhere. All patients tolerated the treatment, with no reduction in QOL outcomes. Patients approached were grateful to have been offered the treatment. The main reason for refusal was monthly travelling for compliance checks. The main adverse comments related to the weight of the mobile battery. One patient had skin irritation, and two patients found that the only aspect of life affected was showering. Two patients have progressed on treatment, with one having second line surgery, and both second line chemotherapy. CONCLUSIONS: Tumour treating fields is a well tolerated but intensive treatment, and acceptable to a UK population. A significant reduction in cost is required to allow routine UK use on the NHS.